Inscription in the Rangamandapa - Temples of India Project Team (Jio Institute, 2024)
The rangamandapa (open type of pillared hall) has revealed a few small inscriptions, one of which can be seen in the projected area on the west. The inscription is found on the moulding that serves as the base for the pillars.